Modelling the capital structure of manufacturing, mining and retail firms listed on the Johannesburg Stock Exchange - Wolmarans, H.P. (Hendrik Petrus) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2013.